Metoda Langkah Demi Langkah Untuk Solusi Transien Rangkaian Listrik - Sukmawidjaja, Maula (Jurnal Teknik Elektro, 2006)
Many complex physical systems are described by differential equations for which a solutioncannot be determined in analytical form. However, techniques are available to obtainapproximate solutions of such differential equations, or sets of equations, by numericalmethods. Thus the solution of differential equations is another important phase in numericalanalysis. In general, methods of numerical integration employ a step-by-step process todetermine a series of values for each dependent variable corresponding to a selected set ofvalues of the independent variable. The usual procedure is to select values of theindependent variable at fixed interval. The accuracy of a solution by numerical integrationdepends both on the method chosen and the size of interval.Keyword: step-by-step, differential equations, numerical methods